1973
DOI: 10.1128/jb.116.3.1364-1374.1973
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Rifampin on the Structure and Membrane Attachment of the Nucleoid of Escherichia coli

Abstract: Deoxyribonucleic acid (DNA) of Escherichia coli was found to be attached to the cell membrane at about 20 points. This was determined by fractionation of X-irradiated cells with the M band (magnesium-Sarkosyl crystals) technique. The number of attachment points was computed from the relationship between the amount of DNA in M bands and the number of double-strand breaks introduced by the X-ray treatment. The number of attachment points was decreased fourfold by treatment of cells with rifampin. This effect was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
3

Year Published

1975
1975
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 126 publications
(73 citation statements)
references
References 37 publications
4
66
3
Order By: Relevance
“…The effect of transcription on domain barrier formation has been tested using the transcriptional inhibitor, rifampicin, but the results were inconclusive. Rifampicin caused chromosomes to decondense upon isolation (Dworsky and Schaechter, 1973;Pettijohn and Hecht, 1974), but did not change the number of domains measured in vivo (Sinden and Pettijohn, 1981).…”
Section: Introductionmentioning
confidence: 83%
“…The effect of transcription on domain barrier formation has been tested using the transcriptional inhibitor, rifampicin, but the results were inconclusive. Rifampicin caused chromosomes to decondense upon isolation (Dworsky and Schaechter, 1973;Pettijohn and Hecht, 1974), but did not change the number of domains measured in vivo (Sinden and Pettijohn, 1981).…”
Section: Introductionmentioning
confidence: 83%
“…Rifampicin affects nucleoid condensation (Morgan et al 1967;Dworsky & Schaechter 1973;Kleppe et al 1979;Vos-Scheperkeuter & Witholt 1982;Sun & Margolin 2004;Kruse et al 2006). Many reports have described the indirect attachment of DNA to the plasma membrane via coupled transcription, translation and translocation of membrane proteins (Kleppe et al 1979;Vos-Scheperkeuter & Witholt 1982).…”
Section: Nucleoid Architecture Inside the Cellmentioning
confidence: 99%
“…Biochemical studies showing reduced sedimentation rate of the isolated nucleoid after RNase treatment have suggested that RNA is situated at the boundaries of nucleoid folding in the core region (Worcel & Burgi 1972;Pettijohn & Hecht 1974). EM studies have shown that the nucleoid shrinks in response to rifampicin treatment, suggesting that RNA anchors the nucleoid to the cell membrane (Dworsky & Schaechter 1973;Kleppe et al . 1979;Vos-Scheperkeuter & Witholt 1982).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the search for a membrane growth zone; on the other hand, studies on attachment sites between DNA and the bacterial envelope. Such sites have been demonstrated [4][5][6][7], including complexes involving the region of the replication origin and the inner membrane of E. coli [8,5]. Similar observations have been made for Bacillus subtilis [9][10][11].…”
Section: Chromosome-envelope Attachment Sitesmentioning
confidence: 53%